Redes extracelulares de DNA de células granulocíticas no escarro de crianças com asma - Silveira, Keila Abreu da (2017)
Background: asthma is a heterogeneous disease characterized by chronic inflammation of the lower airways. The inflammatory process is associated with bronchial hyperresponsiveness, resulting in recurrent episodes of wheezing, coughing, dyspnea and chest tightness. Asthma affects around 300 million people worldwide, with high prevalence, mainly in children. Chronic inflammation in the airways of patients with asthma is complex and involves a range of cells from the immune system, including T lymphocytes, granulocytes, epithelial cells, among others. Granulocytes are considered key cells to maintain inflammation. Neutrophils and eosinophils have different characteristics and functions for the immune response in asthma. Both type of cells release a variety of mediators that contribute to chronic inflammation and changes in the structure of the airways, secondary to external agents. In this context, it was demonstrated that after activation neutrophils and eosinophils are able to release extracellular DNA "traps" with specific proteins that kill extracellular pathogens. On the other hand, it is possible that these DNA "traps" contribute to immunopathology in chronic inflammatory diseases, such as asthma. Therefore, it has recently been shown that neutrophils and eosinophils generate extracellular DNA traps in the airways of asthmatics, possibly contributing to tissue damage. Objective: to verify whether there is extracellular DNA traps and the presence of inflammatory cells in sputum samples of children and adolescents with asthma. Methods: this cross-sectional study selected children and adolescents with asthma, between 6 and 18 years of age, in a regular follow-up at a reference center from southern Brazil. We have performed lung function (spirometry), allergen skin test, and induced sputum to identify the inflammatory cells profile, formation of extracellular DNA traps, and quantification of extracellular DNA. To visualize the extracellular DNA traps, the cells were stained with Hoechst 33342. The images were captured on a fluorescence confocal microscope. Results: 18 children and adolescents were included, 13 with severe asthma and 5 with non-severe asthma. Of these, 17 (94.4%) had a positive skin test for some type of allergens and all patients presented pulmonary function within the limits of normality. Patients with inflammatory cell profiles in sputum (7,12 [4,41,45,23]) showed a significant increase (p = 0.01) in extracellular DNA concentrations compared to patients with pauci-granulocytic profile (2.31 [1.47-3.56]). The extracellular DNA levels correlated positively (r = 0.73, p = 0.004) with the total granulocytic cells in the sputum of these patients. Likewise, there was a significant positive correlation between extracellular DNA and absolute sputum neutrophil counts (r = 0.71, p = 0.008) and absolute sputum eosinophils counts (r = 0.69; p = 0.0013) in the sputum samples. Conclusion: Our results show the presence of extracellular DNA traps in sputum with inflammatory pattern of children and adolescents with asthma suggesting that these traps are released by granulocytic cells, specifically neutrophils and eosinophils.